CLONING AND SEQUENCE ANALYSIS OF PROMOTER ELONGATION FACTOR-1a GENE FAMILY FROM CASSAVA (Manihot esculenta Crantz.) - (NIM 20605021), LIDYA
Elongation factor-1a (EF-1a) is an essential factor for protein synthesis in eukaryotic cells. It catalyzes the binding of aminoacyl tRNA to the A site of the ribosome. Previous evidences show that this protein is encoded by a gene family which consists of more than one copy of EF-1a genes. Three copies of EF-1a genes were found in cassava. One of them was fully characterized including the activity of its promoter (MeEF1a). Based of this evidence, it can be hypotesized that other EF-1a genes have different promoter characteristic. The aim of this study is to clone promoter from different EF-1a gene which is expected to have a different characteristic. PCR-based gene walking was performed to obtain DNA fragment which contained promoter sequence. PCR results were cloned to pGEMT-Easy (Promega) and transform to the host cells E. coli strain DH5a prior to sequencing. Putative promoter EF-1a was characterized based on concensus sequence from literature. Besides gene walking PCR, genomic PCR was performed to estimate the number of genes in an EF-1a gene familiy from cassava. Gene walking PCR resulted in three fragments with ~500, ~700, and ~1200 bp in size. Analysis were then focused on fragment of ~700 and ~1200 bp. Fragment of ~700 bp contains no putative promoter which agreed with the concensus sequence of EF-1a promoter. Fragment of ~1200 bp contains three putative elements which were found to be agreed with the concensus sequence. TATA Box (CTATAAATA) was found -12 bp from TSS (Transcription Start Site), TELO Box (AACCCTAA) was found -11 bp from TATA Box, and TEF1 Box (TGGACAAAATCGT) was found -26 bp from TELO Box. Start codon (ATG) was found +882 bp from TSS and putative 5' UTR intron with 794 bp in length was predicted within this region based on intron splicing site concensus sequence. The same elements were found in cassava MeEF1a gene promoter that has been characterized before. However there are a little differences in its position, sequence, and distance between each box. Besides, there are two putative TATA Boxes in MeEF1apromoter. Therefore, it can be concluded that putative promoter from this study (named MeEF1a2) was different from MeEF1a promoter and might be originated from different EF-1a gene family in cassava. Genomic PCR resulted in four bands with ~300, ~500, ~700, and ~1000 bp in size. It shows that presumably more than four copies of EF-1a gene can be found in cassava EF-1a gene family.